Integrated Supply Chain Planning in Chemical Industry Potentials of Simulation in Network Planning - Kirschstein, Thomas; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2015)
Thomas Kirschstein provides an overview on methods and approaches for planning and optimizing large-scale chemical production networks. The focus is on an integrated modelling of chemical production processes, logistical processes as well as environmental effects. Therefore, a hybrid simulation framework is designed taking into account time series models for modelling chemical production processes, linear optimization models for describing logistical processes as well as stochastic processes for modelling environmental effects. Contents Chemical Production Processes Distribution Planning in Chemical Industry Logistics Integrated Planning of Chemical Supply Chains   Target Groups Researchers and students in the fields of Chemical Supply Chain Management, Chemical Production Networks, Chemical Process Modeling, Operations Management, and Logistics in Chemical Industry Practitioners in these areas  The Author Dr. Thomas Kirschstein wrote his dissertation under the supervision of Prof. Dr. Christian Bierwirth at the Chair of Production and Logistics at the University of Halle (Saale). The Editors The series Produktion und Logistik is edited by Prof. Dr. Christian Bierwirth, Prof. Dr. Bernhard Fleischmann, Prof. Dr. Moritz Fleischmann, Prof. Dr. Martin Grunow, Prof. Dr. Hans-Otto Günther, Prof. Dr. Stefan Helber, Prof. Dr. Karl Inderfurth, Prof. Dr. Herbert Kopfer, Prof. Dr. Herbert Meyr, Prof. Dr. Katja Schimmelpfeng, Prof. Dr. Thomas S. Spengler, Prof. Dr. Hartmut Stadtler, Prof. Dr. Horst Tempelmeier and Prof. Dr. Gerhard Wäscher.
Chemical Production Processes -- Distribution Planning in Chemical Industry Logistics -- Integrated Planning of Chemical Supply Chains.
Keywords: Production management; Operations research; Decision making; Organization; Planning; Operations Management; Operations Research/Decision Theory; Organization